Women in Political Leadership: An Islamic Economic Perspective on Women's Empowerment, Gender Justice and Socio-Economic Welfare - Fitria, Tira Nur (Jurnal Ilmiah Ekonomi Islam, 2025)
This research explores the role of women in political leadership from an Islamic economic perspective, focusing on the interconnectedness of women's empowerment, gender justice, and the socio-economic welfare of the ummah. This research adopts a library research design. The analysis shows that Islamic teachings support women's political leadership, emphasizing justice, competence, and adherence to Islamic values, which include principles of equality, communal welfare, and social well-being. Women's empowerment in Islam is rooted in the recognition of their right to lead and influence society, which is essential for achieving socio-economic development. Through political empowerment, women can shape policies that benefit marginalized communities and promote public welfare. Case studies from Muslim-majority countries, such as Indonesia, demonstrate how women leaders have driven significant reforms in education, poverty alleviation, and economic stability. However, cultural norms, gender stereotypes, institutional barriers, and discriminatory laws still hinder women's political participation. Overcoming these challenges requires societal, legal, and educational reforms based on Islamic principles of justice and equity. Gender justice in Islamic economics advocates for fairness, equality, and dignity, ensuring that both men and women have equal rights, including leadership opportunities. Islamic economic values such as maslahah (public welfare) and balance support women’s inclusion in political leadership, emphasizing competence and ethical governance over gender. Gender justice initiatives, including equal education and employment opportunities, have led to increased participation of women in politics and the workforce, promoting more inclusive socio-economic development. Women's leadership is pivotal in promoting the welfare of the ummah by contributing diverse perspectives to decision-making, particularly on issues like education, healthcare, and poverty alleviation. This involvement enhances inclusive policy-making, aligned with Islamic principles of justice and social welfare. Women's political leadership is crucial for achieving socio-economic prosperity. Women leaders advocate for equitable access to resources, human capital development, and social safety nets, which help reduce inequality and ensure that economic benefits are shared across all segments of society. Gender-sensitive policies, such as fair wages and education reforms, contribute to economic growth and poverty reduction. Despite significant progress, women may still face barriers to leadership due to gender biases, restrictive cultural norms, and patriarchal systems. However, Islamic teachings offer support for overcoming these challenges, emphasizing justice, equality, and the dignity of both men and women. In Indonesia, women's political leadership has grown significantly, with more women now holding positions in the executive, legislative, and judicial branches. This shift reflects societal changes, legal reforms, and a global commitment to gender equality. Islamic economic frameworks provide a foundation for policies that promote women's rights and leadership, supported by Islamic values of adl (justice), musawat (equality), maslahah (social welfare), and maqasid al-shari’ah (objectives of Islamic law).